Varying depth and swarm dimensions of open-ocean Antarctic krill Euphausia superba Dana, 1850 (Euphausiacea) over diel cycles. Issue 6 (24th July 2018) - Tarling, Geraint A; Thorpe, Sally E; Fielding, Sophie; Klevjer, Thor; Ryabov, Alexey; Somerfield, Paul J
Abstract: Diel vertical migration (DVM) behaviour in swarms of Antarctic krill ( Euphausia superba Dana, 1850 ) is notoriously variable, with swarms being found at a range of depths and in different shapes, sizes, and packing concentrations throughout the day-night cycle. Because social aggregation can potentially serve the same purpose as DVM in minimising predation risk, krill may use both strategies to varying extents. Diel variation was examined in swarm depth, length, perimeter, area, thickness, and packing concentration across 4, 130 open-ocean swarms in the Scotia Sea during summer. Inter-relationships between each of the swarm descriptors were complex but multivariate analyses identified pairings in levels of similarity between area and perimeter, thickness and packing concentration, and depth and length. Second-stage analysis further identified diel cyclicity in these relationships. Swarm parameters were more variable than depth over the diel cycle, identifying swarming to be the primary diel response to which DVM is a secondary contributor.